The Effect of Microsoft Power Point Applications on Learning Outcomes of Machine Basics in Class X Department of Light Vehicle Engineering - Kapoh, Timothy Waraney; Lumapow, Harol R.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree; Tuerah, Javier I. (International Journal of Information Technology and Education, 2022)
The purpose of this study was to determine the effect of Microsoft Power Point Application on Learning Outcomes of Basic Machines in Class X Students of the TKR Department of Getsemani Christian Vocational School Manado. This research is included in experimental research. The number of respondents as many as 24 people. This experimental research includes Pre-Experimental (Pre-Experimental) with the type of The Static Group Comparison. The data used in this research is primary data, namely data obtained directly by researchers. The technique used in data collection is by measuring or evaluating in the form of tests on the basics of machines. The result is that there is a significant effect between the control group and the treatment group using the Power Point application in the learning process